Simulated impact of vitamin A fortified sugar on dietary adequacy and association of usual sugar intake with plasma and breast milk retinol among lactating women in rural Zambia - Woldegebreal, Demewoz; Engle-Stone, Reina; Caswell, Bess L.; Luo, Hanqi; Dodd, Kevin; Arnold, Charles; Jobarteh, Modou; Haskell, Marjorie; Palmer, Amanda (American Society for Nutrition, 2021)
Zambia introduced mandatory sugar fortification with vitamin A (VA) in 1998; however, regulatory monitoring and evaluation have been limited. We studied the contribution of VA-fortified sugar intake to dietary adequacy, and examined associations between usual sugar and VA intakes with plasma and breast milk retinol concentrations in lactating women in rural Zambia.